STRATEGI BAURAN PEMASARAN ( MARKETING MIX ) DALAM PERSPEKTIF SYARIAH - Rahim, Endang; Mohamad, Roni (Prodi Ekonomi Syariah Pascasarjana IAIN Sultan Amai Gorontalo, 2021)
Business activities are activities that require serious understanding, starting from planning what will be done, the implementation stage and the stage of monitoring a business being run. In running a business, the important task of marketers is to be able to provide what is needed by the community, both consumers and customers. In order for a business or business that is run to be successful, it would be nice to have an appropriate competitive strategy. This study aims to provide a study and analysis of the marketing mix strategy (Marketing Mix) in the sharia perspective. This type of research is a literature study, data is collected by conducting a review study of previous research journals that are relevant to this research.